The influence of sequential transdermal hormone therapy on serum hormone and lipids profile in perimenopausal women - Skrzypulec, Violetta; Rozmus-Warcholińska, Wioleta; Zdun, Dariusz (Menopause Review/Przegląd Menopauzalny, 2006)
Aim of the study: The evaluation of the effect of sequential transdermal hormone therapy on serum hormone and lipids profile in perimenopausal women. Material and methods: In a six-month (6 treatment periods, 28 days each) randomized study, 75 healthy postmenopausal women aged 48-53(51±3) were assigned to receive 50 micrograms/day of continuous transdermal estradiol with sequential transdermal norethisterone acetate (NETA) in daily doses of 170 micrograms for in a single transdermal patch. Results: Effects on coronary heart disease risk factors, such as reductions in total cholesterol (- 4%; 6±0.9 mmol/l at baseline an 5.9±1.0 mmol/l at the end of the study), low-density lipoprotein cholesterol (-4.6%; 3.7±0.8 mmol/l at baseline and 3.6±0.9 mmol/l after treatment), triglicerydes (-15.4%; 1.6±0.9 mmol/l at baseline and 1.8±1.0 mmol/l after treatment) and significant decrease of high-density lipoprotein cholesterol levels (-17.2%; 1.7±0.4 mmol/l at baseline and 1.4±0.3 mmol/l after treatment) were measured in the treatment group. Nonsignificant dicrease within FSH serum levels (65±33 mIU/ml at baseline and 46±29 mIU/ml at the end of the study) and nonsignificant rise of 17 beta-estradiol (44±81 pg/ml at basleine and 189±236 pg/ml t the end of the study) across treatment were observed. Conclusions: Sequential transdermal estrogen/progestogen hormone therapy with estradiol/NETA appears to be effective and safe for serum hormone and lipids profile in perimenopausal women.